THE INTENTION TO PURCHASE LIFE INSURANCE FROM ISLAMIC PERSPECTIVE: A CASE STUDY AMONG DIPLOMA MUAMALAT STUDENTS IN UITM DUNGUN - Muhammud, Farah Safura; Mustaffa, Yusrina Umaimah (Jurnal 'Ulwan, 2024)
Takaful, commonly referred to as Islamic insurance, is a form of Islamic insurance in which participants make investments into a pooling scheme to indemnify one another against loss or harm. In simple terms, Takaful is an agreement among a group of individuals who agree to jointly compensate damages or losses from a fund they collectively give to. The main premise for takaful-branded insurance is to safe-guard each other. This research objective is to identify the understanding of the life insurance concept from an Islamic perspective, to analyse the factors of intentions in purchasing life insurance, and to identify the awareness of purchasing life insurance among Diploma Muamalat Students in UiTM Dungun. The researcher gathers information used on this subject utilising quantitative methods. Participants are required to fill out a google form that the author distributed to the Muamalat students at UiTM Dungun as part of the quantitative method approach. Based on the results of the study, it is possible to conclude that the target demographic is familiar with the fundamentals of Islamic insurance. The goal of this research is to raise awareness of the intention of purchasing life insurance based on Islamic perspective.